The teaching process through the eyes of teachers’ emotions - Henao, John Fredy; Marín, Andrés Elías (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article presents the findings of the research Anger, joy, and sadness of teachers: an educational point of view, which included public sector teachers in some institutions of the Colombian Department of Caldas. The overall objective revolved around emotions within the classroom; the teacher-student relationships resulting from them were analyzed to understand their mediating role in communication and as an essential element for decision-making regarding teaching. Hermeneutic phenomenology was used as qualitative research approach. The findings allowed for identifying the incidence of emotions in the teaching process and how they affect or improve the development of planned lessons. Drawing on emotional geographies of teaching, it was also found, among other things, that teachers’ emotions often change lesson planning; classes can be more dynamic and they can bring teachers closer to students or, conversely, they can create a distance between them and become more traditional.